Performance of tropical maize hybrids under conditions of low and optimum levels of nitrogen fertilizer application grain yield, biomass production and nitrogen accumulation - Abe, A.; Adetimirin, Victor O.; Menkir, A.; Moose, S.; Olaniyan, A. (2013)
Nitrogen (N) is the most limiting mineral nutrient in the soils of the major maize producing areas of West and Central Africa. Low soil N and sub-optimal application of N fertilizers lead to N deficiency and poor grain yield (GY) in maize. Maize varieties with improved grain yield under low soil N and increased performance under optimal N availability could be beneficial to low input agriculture. This study evaluated the performance of a selection of experimental and commercial hybrids under suboptimal and optimal N fertilizer applications. Significant differences were observed among the hybrids, as well as significant interactions between hybrid and N level for GY and other measured attributes, with the severity of variation increasing as the level of N decreases. Mean GY reductions across the years was 76.5% at no-N and 35.4% at low-N. Depending on N treatment, GY varied from 0.48 to 4.42 Mg ha-1, grain N content from 0.17 to 1.26 g plant-1, total N content at harvest from 0.33 to 2.00 g plant-1, above ground biomass at silking from 30.6 to 91.2 g plant-1 and at maturity from 39.9 to 191.1 g plant-1. Number of kernels was the GY component most severely reduced by N stress and had significant (p = 0.001) positive correlation with GY at all N levels. Six hybrids (4001/4008, KU1409/4008, KU1409/9613, 4008/1808, 4058/Fun 47-4, and 1824/9432) which showed consistent above average grain yields under no-N, low-N, high-N and across N levels were found and their use could further be investigated.